THE USE OF ENGLISH SUBTITLES ON NETFLIX FOR LEARNING ENGLISH: PERCEPTIONS OF ENGLISH EDUCATION STUDY PROGRAM STUDENTS AT SRIWIJAYA UNIVERSITY - Sevati Sheyla Restu Putri; Zuraida Zuraida (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study investigates students’ perceptions of using English subtitles on Netflix as a language learning strategy. The research focuses on how subtitles contribute to the development of English skills, the challenges encountered, and students’ suggestions for effective integration in learning. A mixed-method approach was employed, combining descriptive quantitative data from close-ended questionnaires with qualitative insights from open-ended responses. The participants comprised 41 sixth-semester students from the English Education Study Program at Sriwijaya University, selected through purposive sampling based on their active use of English subtitles on Netflix. Quantitative data were analyzed descriptively to identify patterns in perceptions, while qualitative responses were thematically analyzed. The findings indicate that students perceive significant benefits from using English subtitles, particularly in vocabulary enrichment, listening comprehension, pronunciation, grammar awareness, and exposure to authentic language use. However, challenges such as unfamiliar vocabulary, rapid subtitle speed, divided attention, variation in language styles, and occasional technical issues were also identified. Students’ motivations for using subtitles ranged from intentional language learning to casual entertainment, with many adopting a balanced approach that combines both purposes. Suggestions for maximizing the learning potential of subtitles included selecting appropriate content, integrating short clips into classroom activities, and using subtitles as a fun and engaging learning tool. The study concludes that English subtitles on Netflix serve as both an effective and enjoyable medium for language learning. Their integration into personal and classroom practices can enhance learners’ engagement, autonomy, and exposure to authentic English, thereby supporting long-term language acquisition.